2004
DOI: 10.1023/b:brea.0000036787.59816.01
|View full text |Cite
|
Sign up to set email alerts
|

High Ep-CAM Expression is Associated with Poor Prognosis in Node-positive Breast Cancer

Abstract: Previous studies in small series of patients with invasive breast cancer suggested a prognostic value of Ep-CAM overexpression in primary tumor tissue. To corroborate these findings, we performed a retrospective analysis of Ep-CAM expression using a tissue microarray containing tissue specimens from a large patient set. Ep-CAM expression was evaluated by immunohistochemistry in breast cancer tissue from 1715 patients with documented raw survival data. High level Ep-CAM expression (overexpression) was found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
161
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 17 publications
15
161
0
3
Order By: Relevance
“…Normal-like breast cancer accounted for 7.8% of all breast cancers in 344 breast cancer samples [9] thus forming a substantial breast cancer subgroup. In accordance with our preclinical findings [10], Spizzo et al, showed that 10.3% of 1715 invasive breast cancer patient samples lacked EpCAM expression [11].…”
Section: Introductionsupporting
confidence: 91%
“…Normal-like breast cancer accounted for 7.8% of all breast cancers in 344 breast cancer samples [9] thus forming a substantial breast cancer subgroup. In accordance with our preclinical findings [10], Spizzo et al, showed that 10.3% of 1715 invasive breast cancer patient samples lacked EpCAM expression [11].…”
Section: Introductionsupporting
confidence: 91%
“…12 FABP5 is up-regulated by EpCAM, 37 a tumor-associated epithelial cell adhesion molecule with a negative prognostic effect in breast cancer. 38,39 FABP5 is a major target of the proto-oncogene c-Myc, 40 which is also rapidly up-regulated by de novo expression of EpCAM, 41 and implicated in breast tumor formation and progression. 42 These results suggest an EpCAM-c-Myc-FABP5 link in human breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…With lung, colon, prostate and gastric cancers, we have selected four of the most frequent cancers in the industrialised world. Epithelial cell adhesion molecule expression in breast cancer has been previously published for more than 1700 patient samples (Gastl et al, 2000;Spizzo et al, 2002;Spizzo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As Ep-CAM is involved in adhesion, differentiation and cell proliferation, an influence of Ep-CAM expression on survival of cancer patients can be expected. In breast and gall bladder cancer, patients with high Ep-CAMexpressing primary tumours indeed showed a decreased survival (Gastl et al, 2000;Spizzo et al, 2002;Spizzo et al, 2004;Varga et al, 2004). In clear cell renal cell carcinoma, Ep-CAM expression is infrequent, but patients with Ep-CAM overexpressing tumours show a trend to better survival (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005).…”
mentioning
confidence: 99%